Planning and Democratic Structure in Oil Related Development Areas on Norway’s West Coast - Amdam, Jørgen (AESOP, 2015)
This paper describes how changes in civil society, economic development, communication systems and related changes in the localisation of economic activities and jobs can influence regional structures and integration. The development processes increases the differences between the urban core and the rural periphery, which appears to be changing into three major regional structures with different planning challenges: 1. The large-town belt in the South West, from Stavanger to Bergen that has almost 700.000 inhabitants and 2/3 of all jobs in Western Norway. 2. The small-town belt in the North West, dominant clusters are marine industries related to fisheries, shipbuilding and support services to oil and gas activities. 3. The marginal rural area, comprising fjords, mountains and islands with ¾ of the land, but with less than 1/5 of jobs and population. This area is divided into a lot of small job markets due to the geographical structure. There is no clear “best” alternative for regional political and administrative organisation in Western Norway that can build on an existing “total” integration, mainly due to a lack of infrastructure, networks and intra-regional flows. The region has a lot of conflict lines and differences of interests between coast and inland, urban and rural areas, south and north and maybe only a strong common enemy (the capital Oslo) can unite the area. I have tried to illustrate structures that are possible in the future; the challenge is that they do not exist today but they can be developed by heavy investments and involvement. Instead of establishing political/administrative structures that “fit” existing social and economic patterns, political/administrative reorganisation would be an “instrument” and part of the strategies for the creation of new intra-connected regions, regions that will be relational and geographically
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015